Multi-planar detection optimization algorithm for the interval charging structure of large-diameter longhole blasting design based on rock fragmentation aspects. Issue 12 (2nd December 2018) - Wang, Mingzheng; Shi, Xiuzhi; Zhou, Jian; Qiu, Xianyang
ABSTRACT: The charge structure is an important factor in the adjustment of the energy distribution of explosives and the control of the blasting effect, especially in an underground large-diameter longhole, for interval charge millisecond blasting design. To achieve a reasonable charge structure, a multi-planar detection optimization (MDO) algorithm for charge structures is proposed based on the Harries mathematical model and the superposition method. The vector size of a fragment is transformed into a scalar ruler, and the definition of the spatial non-uniformity evaluation factor is used in the MDO algorithm. A detailed methodology is implemented using a Visual LISP program and validated for a case study of the Fankou lead–zinc mine in China. The results reveal that the MDO algorithm can improve the rock fragmentation and increase the energy utilization rate of explosives in large-diameter longhole blasting operations. This algorithm could be extremely helpful in the process of underground mine blast optimization.